2016
DOI: 10.1016/j.expneurol.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of onabotulinumtoxinA on cardiac function following intradetrusor injections

Abstract: single treatment investigation under resting conditions only. In conclusion, onabotulinumtoxinA intradetrusor injections do not seem to affect resting state cardiac function. Short-term changes such as total power might rather result from natural cardio-vascular responses to the procedure itself (e.g. discomfort, stress). Further detailed investigations also under physical stress and repeated injections are necessary to fully exclude systemic cardiac side effects of onabotulinumtoxinA intradetrusor injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
(66 reference statements)
4
4
0
Order By: Relevance
“…Additionally, no patients showed postoperative need for ISC. This is consistent with the data in the literature ( 24 , 25 ). Miotla et al ( 25 ) described a higher likelihood of postvoid residual volume of more than 200 ml or a need for ISC, but only among elderly patients with a higher rate of pregnancies and vaginal deliveries.…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, no patients showed postoperative need for ISC. This is consistent with the data in the literature ( 24 , 25 ). Miotla et al ( 25 ) described a higher likelihood of postvoid residual volume of more than 200 ml or a need for ISC, but only among elderly patients with a higher rate of pregnancies and vaginal deliveries.…”
Section: Discussionsupporting
confidence: 94%
“…We can speculate that this issue could be incidental or that it is associated with certain psychological factors. A lack of the systemic influence of intradetrusor onabotulinumtoxinA injections on heart function is consistent with previously published research conducted in patients suffering from a neurogenic bladder [ 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…The study showed no effect on the resting state function of the heart, though it had some limitations. One was the lack of patients with cardiac disorders who might be more sensitive towards developing some potential abnormalities in electrocardiograms after treatment [ 18 ]. Therefore, it would be attractive to investigate the influence of onabotulinumtoxinA injections on heart function in patients with pre-existing cardiac arrhythmias.…”
Section: Introductionmentioning
confidence: 99%
“…[35,36] Out of the numerous side effects of BTX injections described in literature in our group of patients we noted no serious adverse events. [37][38][39][40][41][42] For several years, Botulinum toxin has been successfully used in neuromuscular diseases with excessive muscular tension. It used to be administrated to muscles of extremities in children with spastic forms of infantile cerebral palsy.…”
Section: Resultsmentioning
confidence: 99%
“…So in our study, in children, respectively 10-30 units/kg body weight abobotulinum or 2,5-10 units /kg body weight of onabotulinum were used. [33][34][35][36][37][40][41][42][43][44][45][46][47][48][49][50] Estimating the optimal dosage both in children and adolescents is still discussed. Some authors show, both for abobotulinum or onabotulinum, no clear dose-related effect with the observation indicating that a dose greater than 50 U is significantly more effective for certain symptoms of OAB compared with placebo.…”
Section: Resultsmentioning
confidence: 99%